ANALISIS PRODUK BANK SOAL PAI DIGITAL INTERAKTIF DI SD NEGERI 2 BUBAKAN WONOGIRI - Muhamad Samsudin; Mhd. Lailan Arqam; Suyadi; Hanif Cahyo Adi Kistoro; Farid Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The 21st-century digital revolution demands a global educational transformation; however, the evaluation practices of Islamic Religious Education (PAI) at the elementary school level are still dominated by conventional, monotonous, and less interactive paper-based methods. This leads to low learning motivation and slow feedback for students, while teachers face difficulties in managing evaluation data efficiently. Although technological infrastructure such as Chromebooks is available at SDN 2 Bubakan Wonogiri, the utilization of specific digital supporting media for PAI materials remains limited and has not been optimally integrated with pedagogical needs. This study aims to analyze the implementation process, usability, and constraints of using an interactive digital PAI question bank product from the perspective of users (teachers and students) at SD Negeri 2 Bubakan, Wonogiri. This research employs a qualitative approach with a case study design. Data were collected through structured non-participant observation, semi-structured in-depth interviews with the principal, PAI teacher, and students, and product documentation. The results indicate that: (1) The implementation of the digital question bank runs smoothly supported by Chromebook facilities and achieves high material validity aligned with the Kurikulum Merdeka. The product shows good usability with an intuitive interface for elementary students, and successfully runs a formative evaluation function through instant feedback features that reduce student boredom. (2) The constraints faced include full dependency on internet network stability and a lack of question depth, where most items are still textual, focusing on lower-order thinking skills (LOTS) and memorization, thus not yet optimizing affective diagnostic tools to map the internalization of religious values deeply.